PERANAN MADRASAH DINIYAH DARUL FATTAH DESA GALAK KECAMATAN SLAHUNG KABUPATEN PONOROGO DALAM PEMBINAAN AKHLAK ANAK - Dita Mardiana; Rido Kurnianto; Sigit Dwi Laksana (Universitas Muhammadiyah Ponorogo, 2017)
Aqidah Akhlak lesson is also given by formal learning. Junior Islamic School of Darul Fattah seek on founding characters by some activities such as reading Koran which appropriate with proper pronunciation for correct recitation of the Koran and the other lessons, for example Ibadah Amaliyah (Worship Charitable), Qur’an Hadits (Koran and Muhammad guidance), Fiqh (Study of laws pertaining of ritual obligations) and Tarikh Islam (Islam History).The goals of this study are to (1) know the types of founding children’s characters at Islamic Junior School (Madin) Darul Fattah in Galak village, Slahung district, Ponorogo regency, (2) to know the roles of Islamic Junior School (Madin) Darul Fattah within founding children’s character, and (3) to know the booster and demotivating factors of founding children’s character at Islamic Junior School (Madin) Darul Fattah. The approach taken by this research is qualitative. Data collections techniques by interviews, observation, and documentation. To analyze the data used descriptive analysis with reduction data plot, data display, and take verification conclusion, and inductive bethink model.The results showed that (1) the types of founding character in Islamic Junior School Darul Fattah are good and effective, by advice, habitual method, reward and punishment, and providing model. (2 )the roles of founding character make good children’s character to Allah be consistent and responsible for the good worship. Children’s character to themselves and fellow make them to be honest, loving The Messenger of God by doing rawatib prayer, serve devotedly to parents by respect to their parents, and characters to the fellow by helping each other. The result of children’s character to the whole nature by founding character makes children’s attitude care for environment cleanliness. (3) The booster factors of founding characters in Islamic Junior School include self-motivation, parents’ awareness, and motivation from surrounding people. Demotivating factors of founding characters in Islamic Junior School are limited funding and tool and infrastructure aren’t completed yet.